Bipolar Disorder: Identity, Social Support, Religiosity and Spirituality: Can Religiosity/Spirituality be a Mood Balancing Factor? : An Italian Case Report - Santambrogio, Jacopo (Journal of religion and health, 2024)
This paper presents a case study to support the hypothesis that religiosity and spirituality (R/S), as mood balancing factors, could facilitate the recovery process for patients suffering from bipolar disorder (BD) once they have been stabilized and are receiving appropriate support (e.g., in a residential rehabilitative center). After a succinct review of BD and R/S, the patient’s medical history and rehabilitation pathway are described, with a particular focus on the role played by R/S. The authors found that in this case, once the patient was stabilized, R/S helped to consolidate her feelings of well-being, increasing her positive perception of social support services and ultimately her self-confidence.